TINJAUAN YURIDIS MENGENAI KEKEBALAN DIPLOMATIK (IMMUNITY DAN INVIOLABILITY) DI NEGARA KETIGA MENURUT KONVENSI WINA 1961 - Dedi Syahputra Daulay; Sutiarnoto Sutiarnoto; Arif Arif (Journal of USU International Law, 2019)
ABSTRACT Dedi Syahputra Daulay* Dr.Sutiarnoto, S.H.,M.Hum** Arif, S.H.,M.Hum*** Every diplomatic representative carry out the duties and function officially enjoy the freedom to move and inviolability that nobody can interference either in receiving state or the third state. The immunity gives in order to perfom well their duties and fuction. Every single immunity they got should be protected by receiving state or the third state. The immunity itself consist with two parts, immunity and inviolability. Additionally, the immunities not only for its diplomatic repsentative but also for their family, staff even the servant shall enjoy this kind of immunity according to Vienna Convention 1961. This writing used library research approach or normative research, this method is done by collecting data as much as possible that comes from a relevant references which related to the issues, its concist the books, text, journal, jurisprudence, encyclopedia, international law literature, or even international political relation. The method used by normative law research or normative juridical that is a law research as a norm system. The norms that is related as principle, jurisprudence, agreement and doctrine. This research shown that immunity not only applicable in their receiving state but also in the third state while the diplomatic repsentative transit. Many case related to the immunities infringement the diplomatic representative did. One of them is Aljazair Diplomat flying to Brazil while transit in Dutch should face the concequence. The impact of the immunities infringement  not only for the diplomat itself but also the country whom they send them for diplomatic mission. Which eventually, create a state responsibility towards the immunities infringement that diplomat do. Keyword : Diplomatic immunities, Immunity and Inviolability, Third state * Student Faculty of Law University of North Sumatera ** Supervisor I and Lecturer Faculty of Law University of North Sumatera *** Supervisor II and Lecturer Faculty of Law University of North Sumatera